Quality of Life of Participants in a Mind-Body-Based Self-Development Course: A Descriptive Study - Fernros, Lotta; Furhoff, Anna-Karin; W ndell, Per E. (Quality of life research, 2005)
Objective: A cross-sectional survey of quality of life of people attending a self-development course involving psychophysiological mind-body medicine (MBM) activities. Design: A questionnaire study using a health-related quality of life (HRQoL) instrument, the SWED-QUAL, with 13 subscales scored 0-100, and questions about utilisation of alternative and standard health care, medication and sick leave. Setting: A training centre for MBM, established 15 years ago. Study group: One hundred and seven eligible course attendants (response rate 88%, age 20-70 years) during the year 2000 assessed their HRQoL just before entering the course. Attendance was self-initiated, without referral. The results on HRQoL were compared with those of control subjects from the general Swedish population. Results: Six of the thirteen HRQoL subscales were strongly and significantly reduced (p < 0.0001) in the study group: Negative affectivity, Role limitation due to emotional health, Positive affectivity, Cognitive functioning, Family functioning and Marital functioning. Long-term sick leave (>6 months) was three times as frequent in the study group as in the general population. Use of psychotropic medication was slightly increased compared to the general population, at least among the younger male participants. The education level was high, health care utilisation was average and body functioning was good. Conclusions: This group of well-educated men and women gave their emotional health an unexpectedly low rating, on a par with that given by people with chronic diseases.